2020
DOI: 10.1111/jbg.12528
|View full text |Cite
|
Sign up to set email alerts
|

Applying an association weight matrix in weighted genomic prediction of boar taint compounds

Abstract: Biological information regarding markers and gene association may be used to attribute different weights for single nucleotide polymorphism (SNP) in genome‐wide selection. Therefore, we aimed to evaluate the predictive ability and the bias of genomic prediction using models that allow SNP weighting in the genomic relationship matrix (G) building, with and without incorporating biological information to obtain the weights. Firstly, we performed a genome‐wide association studies (GWAS) in data set containing sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 50 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…Therefore, for multi-breed joint genetic evaluation between Xinjiang Brown and Chinese Holstein cattle, considering only the added number of animals is insufficient. Further in-depth analysis of important influencing factors, including assumptions about SNP effects (van den berg et al, 2019) and the weights of the A-and G-matrices in the H-matrix (Karaman et al, 2018;Botelho et al, 2021), is required to improve the accuracy and unbiasedness of predictions (Botelho et al, 2021).…”
Section: Reliability Of Genetic Evaluation In Joint Reference Populat...mentioning
confidence: 99%
“…Therefore, for multi-breed joint genetic evaluation between Xinjiang Brown and Chinese Holstein cattle, considering only the added number of animals is insufficient. Further in-depth analysis of important influencing factors, including assumptions about SNP effects (van den berg et al, 2019) and the weights of the A-and G-matrices in the H-matrix (Karaman et al, 2018;Botelho et al, 2021), is required to improve the accuracy and unbiasedness of predictions (Botelho et al, 2021).…”
Section: Reliability Of Genetic Evaluation In Joint Reference Populat...mentioning
confidence: 99%
“…De Campos et al [19] reported accuracies, measured as the correlation between the observed and the predicted phenotype divided by the square root of trait heritability, equal to 0.63 and 0.57 for AND and SKA, respectively, using a Ridge Regression BLUP method. Lukić et al [59] and Botelho et al [60] estimated the genomic breeding values for AND and SKA through a GBLUP approach with correlations between the predicted breeding values and the phenotypes of 0.27-0.35 and 0.21-0.49 for AND and SKA, respectively. In that study, the accuracies adjusted for the square root of heritability (0.56 and 0.76 for AND and SKA, respectively) were much higher than those obtained in this study.…”
Section: Genomic Predictionsmentioning
confidence: 99%
“…In the literature, only Botelho et al [60] have reported results of genomic prediction for IND: for a dataset consisting of records from a single-line pig population, prediction accuracy computed as the Pearson's correlation between GEBV and phenotypes adjusted for fixed effects ranged between 0.24 and 0.26, whereas for a multi-line pig population, correlations were slightly lower (0.21-0.26). Those correlations are similar to that obtained in the present study.…”
Section: Genomic Predictionsmentioning
confidence: 99%
“…In certain instances, this strategy has resulted in improved accuracy of genomic prediction for growth and carcass traits in pigs, with improvements ranging from 0.9 to 46% for multi-breed populations [21][22][23]. However, it should be noted that this strategy did not result in improved prediction accuracy in all cases [21,24,25]. Fine mapping of causal variants was still challenging, and the advantages for genomic predictions were limited.…”
Section: Introductionmentioning
confidence: 99%